2022
DOI: 10.3389/fmed.2022.856606
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Predictive Model for Adrenocortical Carcinoma Based on Hypoxia- and Ferroptosis-Related Gene Expression

Abstract: BackgroundThe impact of hypoxia on ferroptosis is important in cancer proliferation, but no predictive model combining hypoxia and ferroptosis for adrenocortical carcinoma (ACC) has been reported. The purpose of this study was to construct a predictive model based on hypoxia- and ferroptosis-related gene expression in ACC.MethodsWe assessed hypoxia- and ferroptosis-related gene expression using data from 79 patients with ACC in The Cancer Genome Atlas (TCGA). Then, a predictive model was constructed to stratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Recently, a bioinformatic study has reported that a hypoxia-related gene signature could predict prognosis and reflect the immune microenvironment in ACC ( 126 ). Specifically, based on hypoxia-related gene expression, ACC patients in the TCGA database were divided into three molecular subtypes (C1, C2, and C3), each with different clinical outcomes with C3 having reported of shortest survival ( 127 ).…”
Section: Hypoxia Inducible Factors: Overview Of Structure Function An...mentioning
confidence: 99%
“…Recently, a bioinformatic study has reported that a hypoxia-related gene signature could predict prognosis and reflect the immune microenvironment in ACC ( 126 ). Specifically, based on hypoxia-related gene expression, ACC patients in the TCGA database were divided into three molecular subtypes (C1, C2, and C3), each with different clinical outcomes with C3 having reported of shortest survival ( 127 ).…”
Section: Hypoxia Inducible Factors: Overview Of Structure Function An...mentioning
confidence: 99%